The Role of the Costa Rican College of Social Workers during Covid-19 - Monge Campos, Ana (2023)
Abstract Introduction: Labor conditions worsened during the pandemic, the unemployment of the profession, the decrease in the possibilities of contracting by the State, the oversupply of graduates and the redefinition of some of the positions that were carried out by professionals insocial work. Objective: To provide to professional organizations with the experience of COLTRAS during the pandemic, and how it devoted itself with support and solidarity to the members, who had an emotional, economic and social impact of the pandemic itself and the participation in the execution of actions issued by the National Emergency Commission and by the Ministry of Health. Method and technique: The method used was the systematization of actions, presidency reports and the commissions’ work plans. The techniques used were the virtual sessions, interviews with fellow coordinators of the frontline programs in health, education, municipal and local organizations sectors, among others. The integration and collectivization of experiences was carried out gradually by the secretary of the board with the support of the COLTRAS administrative team. Results: Inequalities and inequities in the population became more visible and vulnerabilities increased in the social work care sectors. The virtuality allowed a greater integration of the subsidiaries at the regional and sectoral level and a greater visualization of the profession. Conclusions: Research, training, systematization and the corresponding dissemination of experiences were strengthened, which strengthened the professional service.   Keywords: Social work, pandemic, vulnerabilities, inequalities, labor conditions.